2023
DOI: 10.1002/bdm.2341
|View full text |Cite
|
Sign up to set email alerts
|

Visual display size and shape impact the accuracy of US adults' health‐risk estimates

Abstract: Health risks, when presented as ratios (e.g., two out of seven people), are challenging to understand, but visual displays can foster accurate understanding. We conducted three experiments to test how characteristics of numbers (Experiment 1), icon arrays (Experiments 1, 2, and 3), and number lines (Experiments 1 and 3) influenced people's ability to accurately estimate the risk of experiencing side effects. Participants in each experiment saw smaller‐ (e.g., 2 out of 7) and larger‐component (e.g., 264 out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 88 publications
(169 reference statements)
1
5
0
Order By: Relevance
“…Consistent with our hypotheses and prior work on the benefits of number line displays (e.g., Fitzsimmons et al, in press; Hamdan & Gunderson, 2017; Mielicki et al, in press; Sidney et al, 2019; Thompson, Taber, et al, 2021), we found that students estimated with less error in the number line ( M = 1.8%, SE = 0.3%) compared to no number line ( M = 2.8%, SE = 0.3%) condition, F (1, 133) = 5.39, p = .022, η p 2 = .04, averaged across grading scale. Additionally, an effect of grading scale, F (2.05, 273.18) = 56.19, p < .001, η p 2 = .30, indicated that, averaged across condition , students estimated with more error in the 387- ( M = 4.5%, SE = 0.4%) and 400-point ( M = 3.5%, SE = 0.4%) courses than the 100- ( M = 0.1%, SE = 0.1%) and 1,000-point ( M = 0.8%, SE = 0.3%) courses ( p < .001), which did not differ, p = .091.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our hypotheses and prior work on the benefits of number line displays (e.g., Fitzsimmons et al, in press; Hamdan & Gunderson, 2017; Mielicki et al, in press; Sidney et al, 2019; Thompson, Taber, et al, 2021), we found that students estimated with less error in the number line ( M = 1.8%, SE = 0.3%) compared to no number line ( M = 2.8%, SE = 0.3%) condition, F (1, 133) = 5.39, p = .022, η p 2 = .04, averaged across grading scale. Additionally, an effect of grading scale, F (2.05, 273.18) = 56.19, p < .001, η p 2 = .30, indicated that, averaged across condition , students estimated with more error in the 387- ( M = 4.5%, SE = 0.4%) and 400-point ( M = 3.5%, SE = 0.4%) courses than the 100- ( M = 0.1%, SE = 0.1%) and 1,000-point ( M = 0.8%, SE = 0.3%) courses ( p < .001), which did not differ, p = .091.…”
Section: Resultssupporting
confidence: 89%
“…Number lines are an effective tool to reduce whole number bias errors and increase accuracy in estimating ratios (Fitzsimmons et al, in press; Mielicki et al, in press; Thompson, Taber, et al, 2021). Number-line visual displays provide people with a quick and easy method to focus on the magnitude of rational numbers (e.g., fractions or decimals) and may help with circumventing potentially erroneous heuristics, such as mistakenly thinking that larger numerators or denominators in fractions equate to larger magnitudes (Booth & Siegler, 2008; Gunderson et al, 2019; Hamdan & Gunderson, 2017; Sidney et al, 2019, 2022).…”
Section: Factors That Affect Students’ Numerical Understandingmentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. (Fitzsimmons, Woodbury, et al, 2022;Mielicki et al, 2021;Sidney, Thompson, & Rivera, 2019; is to visually communicate how the part relates to the whole, and should promote a portable and durable conceptual understanding of rational number magnitudes when people encounter them in various contexts. Though substantial research in health decision-making has examined the use of visuals to help people, especially those low in numeracy, better understand risk magnitudes (Ancker et al, 2006;Bonner et al, 2021;Garcia-Retamero & Cokely, 2013Garcia-Retamero et al, 2012;Trevena et al, 2021), the goal of these visuals is to ease the mathematical burden such that people can more easily comprehend risk magnitudes perceptually (Waters et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another common visual display in health communications is the icon array (Figure 1, Panel D) which includes discrete, countable icons (Galesic et al, 2009;Hess et al, 2011;Zikmund-Fisher et al, 2010). One potential advantage of icon arrays is that they may facilitate translation to percentages, which are likely more familiar (e.g., a file loading from 0% to 100%) and intuitive than other rational numbers (Fitzsimmons, Woodbury, et al, 2022;Moss & Case, 1999;Schiller, 2020). However, icon arrays led to a higher prevalence of WNB than Arabic numerals or number lines for parents estimating the likelihood of side effects from taking a hypothetical drug (Fitzsimmons, Woodbury, et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation